Electronic evidence - Mason, Stephen (LexisNexis, 2010)
Provides you with essential guidance on how to understand electronic evidence and how to use this successfully in litigation and other means of dispute resolution. This title brings together the various issues relating to disclosure, procedure and admissibility of electronic evidence as well as comprehensive coverage of jurisdictions.